(untitled) (Revista Apotheke, 2019)
The process of building art has gone a long way until it reaches the classrooms as an expression of language and a fundamental role of human transformation, to contributing significantly to the child’s cognitive, motor and affective development, as well as enabling its expression and perception of the world. The importance of working with the Visual Arts in the school routine: drawing, painting, modeling, cutting and collage, contributes to the characterization of different languages in the learning process, enabling the development of emotions and the structure for writing. Therefore, the drawing brings in its content the expression of the child’s thinking and feeling, the motor development and acquisitions of their relationship with the social environment. So, it is important to understand how artistic language contributes to the child’s learning, to identify possible methodologies that can be worked on, and to relate the child’s interaction with the surrounding world.